Ischemia in patients with no obstructive coronary artery disease: classification, diagnosis and treatment of coronary microvascular dysfunction. Issue 5 (August 2020) - Sucato, Vincenzo; Novo, Giuseppina; Saladino, Antonino; Rubino, Marianna; Caronna, Nicola; Luparelli, Mirko; D'Agostino, Alessandro; Novo, Salvatore; Evola, Salvatore; Galassi, Alfredo Ruggero
Abstract : Patients with coronary microvascular dysfunction represent a widespread population, and despite the good prognosis, many of them, because of the angina symptoms, have a poor quality of life with strong limitations in their daily activities. In 2017, a new classification of microvascular dysfunction as well as a new definition of ischemia in patients with no obstructive coronary artery disease became available. This new definition improves Kemp's initial work, where cardiac X syndrome was initially described. This work summarizes the last updates on the subject with particular attention to the new classification of microvascular dysfunction, with particular attention to microvascular and vasospastic angina definition and diagnostic criteria.